2023
DOI: 10.1007/s11187-023-00730-0
|View full text |Cite
|
Sign up to set email alerts
|

ECB unconventional monetary policy and SME access to finance

Abstract: Small- and medium-sized enterprises (SMEs) account for two-thirds of employment in the euro area which makes them a priority for the transmission of monetary policy to the real economy. SMEs in Europe experienced a credit crunch following the sovereign debt crisis. Over the period 2014–2019, the European Central Bank (ECB) engaged in unconventional monetary policy (UMP) to restore funding conditions in the euro area, to support stronger economic growth and higher inflation. We use the ECB/EC Survey on the Acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 86 publications
1
6
0
Order By: Relevance
“…Depending on the different countries and analyses applied, the evidence presents mixed results. Finnegan and Kapoor (2023) showed a link between monetary policy and SMEs' finance in Greece, Ireland, Italy, Portugal, and Spain, and confirmed that in stressed (non-stressed) countries, monetary policy significant (insignificant) raises the likelihood that SMEs with higher debt remain credit conditioned. They find that because risky firms are creditconstrained, monetary policy is unevenly diffused to leveraged SMEs.…”
Section: Literature Reviewsupporting
confidence: 55%
See 2 more Smart Citations
“…Depending on the different countries and analyses applied, the evidence presents mixed results. Finnegan and Kapoor (2023) showed a link between monetary policy and SMEs' finance in Greece, Ireland, Italy, Portugal, and Spain, and confirmed that in stressed (non-stressed) countries, monetary policy significant (insignificant) raises the likelihood that SMEs with higher debt remain credit conditioned. They find that because risky firms are creditconstrained, monetary policy is unevenly diffused to leveraged SMEs.…”
Section: Literature Reviewsupporting
confidence: 55%
“…However, some studies consider the influence of fiscal policies to stimulate SMEs' performance (Zhang and Wang, 2023). Further, many studies, including Ferrando et al (2019), Moreira et al (2016), Fu and Liu (2015), Fasano and La Rocca (2023), Finnegan and Kapoor (2023), found a link between monetary policy to SMEs. Zhang and Wang (2023) reported how the Chinese government policies over the years influence SMEs and other businesses.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…SMEs need human bankers, and personal contacts cannot be fully replaced by digitalization. For instance, the discretion of a loan officer can hardly be substituted by digitalization, and this is particularly important for informationally opaque SMEs, whose access to external finance is very important (Finnegan & Kapoor, 2023). Thus, a key implication of our findings is that the importance of bank-firm geographical closeness is changing, which means that in the near future, banking institutions will have to rethink their business models in light of the ongoing growth of digitization.…”
Section: Introductionmentioning
confidence: 90%
“…Mateev et al (2013) identified a significant correlation between BAge and SMEs' preference for specific finance sources. Additionally, Wignaraja and Jinjarak (2015) found a positive association between an SME's BAge and the utilization of bank loans, while Mohamed Zabri et al (2021) and Finnegan and Kapoor (2023) concluded that a negative relationship exists between an SME's BAge and reliance on debt as a source of external finance. Numerous researchers have also extensively examined the association between enterprise age and business risks (Nguyen and Vo 2020).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%